Analisis Dampak Kebijakan Ecotourism di Wisata Alam Bukit Lawang Bagi Perekonomian Masyarakat - Eski Aditya; Nurul Jannah; Budi Dharma (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to analyze how the impact of the existence of ecotourism policies implemented in Bukit Lawang nature tourism has on the community's economy. The research method used in this study is a qualitative descriptive method, namely by using an analysis of events, phenomena or social conditions. Source of data used is primary data. There are three data collection methods used, namely observation, interviews and documentation. Data validity techniques for data validity used in this study are source triangulation and method or technique triangulation. The results of this study indicate that the impact of the existence of ecotourism policies on Bukit Lawang nature tourism has a positive effect on several things, such as: reducing unemployment, increasing people's economic income, surrounding area income, utilization of natural resources and good human resources and also enhance nature conservation efforts. In addition, the sustainability of ecotourism requires collaboration or cooperation between tourism managers and the local community. Keywords: Ecotourism Policy, Community Economy